2021
DOI: 10.21037/jtd-19-3716
|View full text |Cite
|
Sign up to set email alerts
|

Managing complications of percutaneous tracheostomy and gastrostomy

Abstract: Percutaneous tracheostomy and gastrostomy are some of the most commonly performed procedures at bedside in the intensive care unit. While they are generally considered safe, they can be associated with numerous short and long-term complications, many of which can occur long after their placement and cause significant morbidity. Performers of these procedures should possess a comprehensive understanding of procedural indications and contraindications, and know how to recognize and manage complications that may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 127 publications
(180 reference statements)
0
25
0
2
Order By: Relevance
“…In patients with percutaneous tracheostomy, almost half of patients bled at the insertion site. Bleeding was also the most common complication of tracheostomy in the current report [ 15 ]. Nevertheless, some previous studies reported bleeding complications at 0.6–5% [ 16 ].…”
Section: Discussionmentioning
confidence: 90%
“…In patients with percutaneous tracheostomy, almost half of patients bled at the insertion site. Bleeding was also the most common complication of tracheostomy in the current report [ 15 ]. Nevertheless, some previous studies reported bleeding complications at 0.6–5% [ 16 ].…”
Section: Discussionmentioning
confidence: 90%
“…It was found that, due to retrocollis, the trachea was deformed into a C curve and the tip of the tracheostomy tube had attached to the tracheal anterior wall, where the innominate artery transverses. The relationship between tracheal anterior wall compression by the tip of the tracheostomy tube and TIF formation has previously been reported [ 4 - 6 ]. From our CT findings and evidence from the literature, our patients were considered to be at high risk of developing TIF.…”
Section: Discussionmentioning
confidence: 99%
“…Neck deformity is one of the contributing factors to TIF formation [ 2 , 4 ]. Our two patients with PD and MSA showed a neck extension deformity, so-called retrocollis, after tracheostomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A percutaneous endoscopic gastrostomy (PEG) tube is a standard feeding modality for patients requiring long-term enteral feeding support [1,2], and its use has been increasing since the 1980s [3][4][5]. Buried bumper syndrome (BBS) is a rare but serious long-term complication of PEG tube feeding [6][7][8] and has a prevalence of 1.5% to 9% [2,6].…”
Section: Introductionmentioning
confidence: 99%